United States of America. Significant achievements 2010 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in the United States during 2010 are identified, with respect to the needs and interests of the country, strengthening topics such as research, technology, safety, innovation, financing, distance education, production, food security, agriculture. family, insurance, sustainability and training. Finally, technical assistance was provided in the exchange of knowledge, protocols, agricultural libraries, risk management, natural resource management, resilience against climate change, attention to natural disasters, production of basic crops, fruits and mangoes, and disease control. such as the H1N1 virus and animal influenza.